Mechanisms regulating the sorting of soluble lysosomal proteins. Issue 5 (27th May 2022) - Meraş, İçten and Maes, Juliette and Lefrancois, Stephane
Abstract: Lysosomes are key regulators of many fundamental cellular processes such as metabolism, autophagy, immune response, cell signalling and plasma membrane repair. These highly dynamic organelles are composed of various membrane and soluble proteins, which are essential for their proper functioning. The soluble proteins include numerous proteases, glycosidases and other hydrolases, along with activators, required for catabolism. The correct sorting of soluble lysosomal proteins is crucial to ensure the proper functioning of lysosomes and is achieved through the coordinated effort of many sorting receptors, resident ER and Golgi proteins, and several cytosolic components. Mutations in a number of proteins involved in sorting soluble proteins to lysosomes result in human disease. These can range from rare diseases such as lysosome storage disorders, to more prevalent ones, such as Alzheimer's disease, Parkinson's disease and others, including rare neurodegenerative diseases that affect children. In this review, we discuss the mechanisms that regulate the sorting of soluble proteins to lysosomes and highlight the effects of mutations in this pathway that cause human disease. More precisely, we will review the route taken by soluble lysosomal proteins from their translation into the ER, their maturation along the Golgi apparatus, and sorting at the trans-Golgi network. We will also highlight the effects of mutations in this pathway that cause human disease.